Design of an Internet of Things (IoT) Based Composter Monitoring System Using Arduino Leonardo, ESP-01S, DHT-11, MQ-4 and Blynk - Tatik Juwariyah; Achmad Zuchriadi P; Santika Sari (Fakultas Ilmu Komputer, 2026)
Conventional methods of manually monitoring compost parameters are often inefficient and susceptible to human error. To address this, this study conducted an Internet of Things (IoT) smart composter system designed to track the fermentation process in real-time. The system architecture integrated Arduino Leonardo microcontroller with DHT-11 sensor for temperature and humidity, and MQ-4 sensor to detect the methane concentrations indicative of anaerobic activity. Data were transmitted via ESP-01S Wi-Fi module to the Blynk cloud platform for visualization. A ten-day performance test, with data recorded at six-hour intervals, demonstrated the system's ability to accurately capture the physical fluctuations inherent in decomposition. The results highlighted a temperature rise over five days peaking at 38.7°C, humidity saturation reaching 95.8% RH, and a maximum methane concentration of 218 ppm on the fourth day. Therefore, this system presented a robust technological intervention for agricultural practitioners, facilitating the precise, efficient, and real-time surveillance of compost bins.